2022
DOI: 10.1089/brain.2020.0935
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Risk Factors Modify Hubs but Leave Other Connectivity Measures Unchanged in Asymptomatic Individuals: A Graph Theoretical Analysis

Abstract: Dementia risk factors modify hubs but leave other connectivity measures unchanged in asymptomatic individuals: a graph theoretical analysis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Our study is the first to examine changes in rT1w/T2w ratio maps associated with a parental history of AD. Similarly to the group showing the co-occurrence of APOE4 and FH, the FH group exhibited higher rT1w/T2w ratio levels in fronto-temporal regions and lower rT1w/T2w ratios in the right paracentral lobule, a cortical hub able to distinguish between individuals at low and high risk of developing AD [ 45 ]. Multiple lines of evidence have shown that early Aβ pathology could manifest either as focal myelin loss in AD patients and transgenic mouse models of AD [ 46 , 47 ] or as an increase in oligodendrogenesis paralleled by thicker myelin sheaths in hippocampal axons of transgenic mouse models of AD [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is the first to examine changes in rT1w/T2w ratio maps associated with a parental history of AD. Similarly to the group showing the co-occurrence of APOE4 and FH, the FH group exhibited higher rT1w/T2w ratio levels in fronto-temporal regions and lower rT1w/T2w ratios in the right paracentral lobule, a cortical hub able to distinguish between individuals at low and high risk of developing AD [ 45 ]. Multiple lines of evidence have shown that early Aβ pathology could manifest either as focal myelin loss in AD patients and transgenic mouse models of AD [ 46 , 47 ] or as an increase in oligodendrogenesis paralleled by thicker myelin sheaths in hippocampal axons of transgenic mouse models of AD [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that co-occurrence of APOE4 and FH of AD has synergistic effects on tissue integrity in normal-appearing cortical GM, which further lead to aberrant patterns of rs-FC. The precentral gyrus showed abnormal FC with the precuneus and paracentral gyrus of the right hemisphere, which are early myelinating regions involved in AD [ 53 ] and affected by non-modifiable AD risk factors [ 45 ]. In addition, the precentral gyrus, one of the cortical areas containing the highest density of myelinated axons in the human neocortex [ 17 ], exhibited lower relative T1w/T2w ratios bilaterally in individuals with APOE4+FH.…”
Section: Discussionmentioning
confidence: 99%
“…Besides regions involved in executive function and memory, the APOE3 versus APOE4 comparison emphasized the role of sensory and motor areas including vision (V1), taste, and pain (insula, periaqueductal gray). Sensory and motor associated regions have also been found to differ in asymptomatic APOE4 carriers relative to APOE3 carriers (Clarke, Messaritaki et al 2022). We noted connectivity differences for the cerebellum, which has a well-known role in movement control but also in language processing, learning and memory (Koziol, Budding et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Ma et al (2017) observed that the values for the APOE4 carriers were higher than those of the non-carriers in a normal-cognition group, while the opposite pattern was observed in a group of participants suffering from Mild Cognitive Impairment (MCI). Middle-aged adults with genetic, family and lifestyle risks of developing AD have a hub in their structural connectome that is not present in the structural connectome of people with no such risks of developing AD ( Clarke et al, 2020 ). Significant functional connectivity differences in the brain networks implicated in cognition were seen in middle-aged individuals with a genetic risk for AD ( Goveas et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%